Kesalahan Siswa Dalam Menyelesaikan Soal Trigonometri Kelas X SMA Negeri 1 Kartasura Tahun Ajaran 2016/2017 - Lestari, Puji; , Rita Pramujiyanti Khotimah,M.Sc (2017)
This study is aimed to describe error by students and factor makes cause to be students in solving trigonometry. This research is descriptive qualitative research, who subject of research are students Tenth grade MIPA 5 of SMA N 1 Kartasura in academic year 2016/2017. The methods of collecting data are documentation and interview. The credibility of data using triangulation techniqu. To analyze the data the writer takes of reducing, dispaly and drawing conclusion. The result of this research shows that Students make in solving trigonometry question is error concept many 71,04%, error strategy many 60,52% and error calculation many 18,41%. (1) Error in concept, that factor causes of low understanding by students, difficulty in read of information, less to try of same question by students, students forget formula trigonometry and less of understanding material about trigonometry. (2) Error in strategy, cause of less in try to doing of exercise, students a hurry to do the trigonometry question of comparative, the angle in relation, the eqution of simple, trigonometry identity, and low of retention students in the use of correct formula. (3) Error in calculation, cause of the students isn't very thorough in doing exercise, students don't correcting again the task, and students feel thorough and panic to do exercice, and students less the control basic of algebra. This study shows the most error by students is concept. Keyword: Trigonometry, error, conceptual, strategy, calculation.